2020
DOI: 10.21037/jgo.2019.06.01
|View full text |Cite
|
Sign up to set email alerts
|

Downstaging unresectable hepatocellular carcinoma by radioembolization using 90-yttrium resin microspheres: a single center experience

Abstract: Background: Only one third of patients with hepatocellular carcinoma can benefit from curative treatments at the time of first diagnosis. Tumor downstaging by radioembolization may enable initially unresectable hepatocellular carcinoma (HCC) to be treated with surgery lengthening survival. Methods: From June 2011 through June 2014, all patients with a first diagnosis of unresectable HCC with intrahepatic portal vein thrombosis were treated in our center with radioembolization using 90-yttrium resin microsphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Tabone et al. used radioembolization to downstage unresectable HCC, and 5 of 24 (20.8%) patients were downstaged to surgery ( 24 ). Lee et al.…”
Section: Discussionmentioning
confidence: 99%
“…Tabone et al. used radioembolization to downstage unresectable HCC, and 5 of 24 (20.8%) patients were downstaged to surgery ( 24 ). Lee et al.…”
Section: Discussionmentioning
confidence: 99%
“…TARE can be used with safety in patients with portal vein thrombosis (PVT) for its low risk of liver ischemia 16,17 . It has been successfully performed in downstaging strategy to liver transplantation or surgical resection 18–20 …”
Section: Introductionmentioning
confidence: 99%
“…Eight retrospective studies [ 5 , 28 , 32 , 34 , 37 , 38 , 40 , 42 ] have also found a significant survival benefit in patients of whom the tumour dose reaches their reported threshold (range 100–205 Gy), most of which are a two to threefold increase in overall survival.…”
Section: Resultsmentioning
confidence: 99%
“…One study has attempted to make an estimation of the T/N ratio by incorporating the hypervascularization status (based on CT imaging) into a volumetric partition model [30]. A total of 11 studies have predicted the tumour doses based on 99m Tc-MAA SPECT [5,12,26,[31][32][33][34][35][36][37][38], four have imaged the microsphere distribution with 90 Y-SPECT [39][40][41][42], and six studies have utilized 90 Y-PET [3,12,[43][44][45][46]. This has also resulted in a very wide range of reported dose thresholds, varying from 61 Gy to 1000 Gy, with the majority being between 100 and 250 Gy (13/19 studies; 68%).…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%